Remembering Sofya Kovalevskaya - Audin, Michele; SpringerLink (Online service). (London New York Springer, 2011)
Sofia Kovalevskaya was a brilliant and determined young Russian woman of the 19th century who wanted to become a mathematician and who succeeded, in often difficult circumstances, in becoming arguably the first woman to have a professional university career in the way we understand it today. This memoir, written by a mathematician who specialises in symplectic geometry and integrable systems, is a personal exploration of the life, the writings and the mathematical achievements of a remarkable woman. It emphasises the originality of Kovalevskayas work and assesses her legacy and reputation as a mathematician and scientist. Her ideas are explained in a way that is accessible to a general audience, with diagrams, marginal notes and commentary to help explain the mathematical concepts and provide context.This fascinating book, which also examines Kovalevskayas love of literature, will be of interest to historians looking for a treatment of the mathematics, and those doing feminist or gender studies.
Sofyas chronology -- Sofyas names -- Stories -- The thesis of Sofya, the Cauchy Kovalevskaya theorem -- The Solid -- A letter to Mittag-Leffler -- Stockholm -- A letter to Vollmar -- The Bordin prize and Sofyas reputation -- The women of Men of mathematics -- I remember Sofya, by George, Gosta, Julia and all the rest -- I too remember Sofya -- Bibliography.
Electronic reproduction.
Keywords: Kovalevskai︠a︡, S. V. -- 1850-1891.; Women mathematicians -- Russia -- Biography; Electronic books